Analisis Website Tapanuli Tengah Menggunakan Metode Open Web Application Security Project Zap (Owasp Zap) - Khairrun Nisa; Muklas Adi Putra; Rizky Akbar Siregar; Muhammad Dedi Irawan (Bulletin of Information Technology (BIT), 2022)
Data security on the website is very important to prevent misuse of data or information on the website. Due to the rapid advancement of technology, many irresponsible persons who are often called hackers or hackers steal data. The author is interested in learning more about the security of the Central Tapanuli website (TAPTENG) as a result of this research. In this section, the author checks the security of the Tapanuli Tengah website using the OWASP ZAP method to assist in determining the actions that need to be taken to mitigate the vulnerability. There are several stages of OWASP that are carried out including Information Gathering, Session Management Testing, Data Validation Testing, and Webservices Testing. From the overall research results detected on the 192.187.99.170 website, the results obtained were 22079 instances with the threat name Timestamp Disclosure - Unix with the threat level at the Low level, which means it is at a low level.